Contrast-induced nephropathy after recanalization chronic coronary occlusion in patients with renal artery stenosis and normal creatinine levels - N. A. Yaitskiy; O. G. Zverev; A. V. Voynov; S. M. Lazarev; A. I. Azeyan; A. F. Bokov (Вестник хирургии имени И.И. Грекова)
Introduction. Contrast-induced nephropathy (CIN) is a complication that occurs after contrast medium (CM) administration. The existing risk scales for possible CIN include chronic kidney disease and do not take into account stenotic changes in the renal artery with normal serum creatinine levels.The Objective was to study the frequency of CIN in patients with acute and chronic coronary occlusion (CCO) after endovascular recanalization in the presence of hemodynamically significant renal artery damage with initially normal creatinine levels.Methods and Materials. The study included 38 patients with acute coronary syndrome (control group) and 67 patients with CCO and hemodynamically significant renal artery stenosis (main group). Stenting of one of the renal arteries was performed in 25 patients out of 67 patients before planned coronary revascularization.Results. The incidences of CIN were significantly higher than the calculated one in patients with CCO and renal artery stenosis. In the group of patients with pre-stenting of the renal arteries, there was a decrease in cases of CIN.Conclusions. Renal artery stenosis with normal creatinine levels is an additional risk factor for CIN.